Strategies for Improving Employee Performance in The Agriculture Services of Central Kalimantan Province - Hansly; Rita Yuanita Toendan; Peridawaty (Indonesian Journal of Economic & Management Sciences, 2024)
This research discusses the Human Resources strategy implemented in the Central Kalimantan Provincial Agriculture Service and its impact on improving employee performance. The main focus of this research is to evaluate the extent to which human resource strategies, such as training, competency development, and career management, have influenced individual and organizational performance as a whole. By involving 30 respondents from various positions in the Department of Agriculture, the research results showed that the majority of employees were aware of the importance of human resource strategies in increasing their work effectiveness. As many as 75% of respondents reported an increase in individual performance, while 80% stated that existing human resource policies had contributed to the operational efficiency of the department. However, the research also identified several challenges, such as the need for more specific training and support in career development. Overall, effective human resource strategies have been proven to increase employee motivation, job satisfaction and performance, although improvements are still needed in several areas to achieve optimal results. This research concludes that planned and focused human resource management can contribute significantly to improving organizational performance and public services in the agricultural sector